Respostas
respondido por:
1
usando a regra do quociente
![\boxed{\boxed{\left( \frac{U}{V} \right)' = \frac{U*V'-U*V'}{V^2} }} \boxed{\boxed{\left( \frac{U}{V} \right)' = \frac{U*V'-U*V'}{V^2} }}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7B%5Cleft%28+%5Cfrac%7BU%7D%7BV%7D+%5Cright%29%27+%3D++%5Cfrac%7BU%2AV%27-U%2AV%27%7D%7BV%5E2%7D+%7D%7D)
aplicando isso no problema
![f(x)= \frac{ln(x)}{x} \\\\ f'(x)= \frac{[ln(x)]'*x - ln(x)*[x]'}{x^2} \\\\f'(x)= \frac{[ \frac{1}{x} ]*x-ln(x)*[1]}{x^2} \\\\f'(x)= \frac{ 1-ln(x) }{x^2} f(x)= \frac{ln(x)}{x} \\\\ f'(x)= \frac{[ln(x)]'*x - ln(x)*[x]'}{x^2} \\\\f'(x)= \frac{[ \frac{1}{x} ]*x-ln(x)*[1]}{x^2} \\\\f'(x)= \frac{ 1-ln(x) }{x^2}](https://tex.z-dn.net/?f=f%28x%29%3D++%5Cfrac%7Bln%28x%29%7D%7Bx%7D+%5C%5C%5C%5C+f%27%28x%29%3D+%5Cfrac%7B%5Bln%28x%29%5D%27%2Ax+-+ln%28x%29%2A%5Bx%5D%27%7D%7Bx%5E2%7D+%5C%5C%5C%5Cf%27%28x%29%3D+%5Cfrac%7B%5B+%5Cfrac%7B1%7D%7Bx%7D+%5D%2Ax-ln%28x%29%2A%5B1%5D%7D%7Bx%5E2%7D+%5C%5C%5C%5Cf%27%28x%29%3D+%5Cfrac%7B+1-ln%28x%29+%7D%7Bx%5E2%7D+)
aplicando isso no problema
paulomagnofleit:
Vlw
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás